2017
DOI: 10.1016/j.commatsci.2016.11.048
|View full text |Cite
|
Sign up to set email alerts
|

Mesoscopic coupled modeling of texture formation during recrystallization considering stored energy decomposition

Abstract: Microstructure-based simulations were performed to understand the mechanism involved with texture formation during recrystallization in polycrystalline interstitial free (IF) steel. The crystal plasticity finite element method (CPFEM) was used to simulate mesoscopic deformation with its heterogeneity. The orientation components were decomposed according to the stored deformation energy, and the results were used to define potential candidates for nucleation sites. On the basis of the oriented nucleation approa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(9 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…Simulation studies on microstructure evolution during recrystallization for a single-pass process have been performed by utilizing a CA model [ 9 , 10 , 11 ] and combining the CA method with the finite element method (FEM) [ 12 , 13 ] or the crystal plasticity finite element method (CPFEM) [ 14 , 15 , 16 ]. Those studies investigated the mesoscale grain structural evolution as well as the macro- or meso-scale mechanical response.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Simulation studies on microstructure evolution during recrystallization for a single-pass process have been performed by utilizing a CA model [ 9 , 10 , 11 ] and combining the CA method with the finite element method (FEM) [ 12 , 13 ] or the crystal plasticity finite element method (CPFEM) [ 14 , 15 , 16 ]. Those studies investigated the mesoscale grain structural evolution as well as the macro- or meso-scale mechanical response.…”
Section: Introductionmentioning
confidence: 99%
“…As a result of inherent experimental difficulties, these studies cannot fully elucidate the physical mechanisms contributing to grain refinement, because one needs to consider the temporal evolution of the multi-pass processes of recrystallization and the γ→α transformation, With the development of technologies in computer science, numerical simulation methods have popularized and become an important tool for understanding the mechanisms of microstructure formation during material processes due to their capabilities to present the visual, temporal evolution of microstructures. Among different numerical models, the cellular automata (CA) approach, combining both computational efficiency and simplicity [8], has been commonly applied to investigate various phenomena such as recrystallization [9][10][11][12][13][14][15][16][17][18][19][20][21][22], phase transformation [23][24][25][26][27][28][29][30][31], and grain coarsening [32,33].…”
Section: Introductionmentioning
confidence: 99%
“…Characterization and understanding of these deformation heterogeneities and the associated microstructural evolution during plastic deformation play a critical role in identifying the underlying mechanisms behind many physical phenomena. For instance, a thorough physical understanding of the mechanisms leading to recrystallization is not feasible without properly characterizing microstructural evolution during plastic deformation [1][2][3][4][5][6][7] . Moreover, damage formation, fracture, and failure in metals are also often related to deformation localization and microstructures formed during deformation [8][9][10][11] .…”
Section: Introductionmentioning
confidence: 99%
“…They also found that most of the energy stored in the dislocations is associated with their long-range stress fields (back stress), which accounted for more than 95%. Recently, mesoscopic microstructure-based modeling approaches such as crystal plasticity finite element method (CPFEM), have been popular for calculating the stored energy in a heterogeneous polycrystalline [ 25 ]. However, those methods are too complex to be used in engineering applications.…”
Section: Introductionmentioning
confidence: 99%